Protease-activated receptor 2 promotes clearance of Pseudomonas aeruginosa infection by inducing cAMP-Rac1 signaling in alveolar macrophages - Rayees, Sheikh; Joshi, Jagdish Chandra; Joshi, Bhagwati; Vellingiri, Vigneshwaran; Banerjee, Somenath; Mehta, Dolly (Frontiers in Pharmacology, 2022)
Efficient phagocytosis of pathogens by the innate immune system during infectious injury is vital for restoring tissue integrity. Impaired phagocytosis, such as in the case of infection with Pseudomonas aeruginosa, a broad-spectrum antibiotic-resistant Gram-negative bacterium, can lead to a life threatening lung disorder, acute lung injury (ALI). Evidence indicates that loss of protease-activated receptor 2 (PAR2) impaired Pseudomonas aeruginosa clearance leading to non-resolvable ALI, but the mechanism remains unclear. Here, we focused on the alveolar macrophages (AMs), the predominant population of lung-resident macrophages involved in sensing bacteria, to understand their role in PAR2-mediated phagocytosis of Pseudomonas aeruginosa. We found that upon binding Pseudomonas aeruginosa, PAR2-expressing but not PAR2-null AMs had increased cAMP levels, which activated Rac1 through protein kinase A. Activated Rac1 increased actin-rich protrusions to augment the phagocytosis of Pseudomonas aeruginosa. Administration of liposomes containing constitutively active Rac1 into PAR2-null mice lungs rescued phagocytosis and enhanced the survival of PAR2-null mice from pneumonia. These studies showed that PAR2 drives the cAMP-Rac1 signaling cascade that activates Pseudomonas aeruginosa phagocytosis in AMs, thereby preventing death from bacterial pneumonia.